Multilingualism – a new old approach to learning and teaching (foreign) languages - Jazbec, Saša (Slavia Centralis, 2022)
The paper explores the concept of translanguaging. It may be considered, in fact, as a new-old concept, since it reflects a method of communication that has always been used spontaneously and unconsciously by speakers of different languages in different communicative situations. It is also a new concept because it has yet to be established in institutional frameworks. This paper’s purpose is to describe and present the concept of translanguaging from a theoretical point of view and in comparison with code-switching. We are particularly interested in its potential within the pedagogical framework of learning and teaching foreign languages, as the concept places all languages, i.e., both foreign and all the students’ mother tongues, in a more equal position. The theoretical starting points will be illuminated by the findings of an illustrative pedagogical experiment.